Livelihood and Food Security Status of Squatter and Street-side Dwellers of Dhaka City (Bangladesh Journal of Nutrition, 2020)
The objective of this study was to identify the livelihoods and food security conditions of the people migrating from rural to urban squatters and street sides of Dhaka City. The study was cross-sectional. Socio-demographic, economic, food security and livelihoods data were collected. Food security was assessed by Food Access Survey Tool (FAST) and Coping Strategy Index (CSI) method. A total of 340 households from squatter (n=209) and street-side dwellers (n=131) were selected using the convenience sampling method. A Student t-test and a Chi-square test were used to detect group differences between the squatter and street-side dwellers. Almost all households were food insecure in both settlements while about half of the street households and one-fourth of the squatter households were severely food insecure. About half of the families borrowed food from neighbours/relatives or substituted wheat or another grain for rice. In squatter households, monthly income was slightly higher than the street households, but they both spend around 58%-62% of their income on food. About 73% of the street parents and 50% of the squatter parents were illiterate. The majority of squatter households had tin walls constructed on soil (51.7%) or a semi-concrete floor (45.9%) while street households were living in portable shanties/Jhupri (50.4%) or non-government organization (NGO) centres (20.6%), with limited access to power and cooking facilities. In both settings, most households used iodized salt and open-packaged oil for cooking. However, over 60% of the households in both settlements had at least one smoker while 19% of the street households had at least one drug-addicted person. Study findings indicate that both squatters and street-side dwellers are suffering from a severe form of food insecurity and maintaining a low standard of living. Immediate attention is required to improve food insecurity either through financial assistance, skill training, or small-scale business opportunities.Bangladesh J. Nutr. Vol. 33, December 2020, P: 53-64